Electrical discharge grinding of polycrystalline diamond – Effect of wheel rotation. Issue 1 (2nd January 2016) - Rahim, M. Zulafif; Ding, Songlin; Mo, John
ABSTRACT: Electrical Discharge Grinding (EDG) is an advanced machining process that becomes popular in manufacturing of Polycrystalline Diamond (PCD) tools. This research investigated the effects of wheel rotation as well as debris flow direction on the quality of PCD tools based on a series of EDG experiments. Experimental results showed the debris that flowed toward the cutting edge could significantly affect the edge sharpness and symmetry of the tool, which were critical for the smaller edge apex angle. Evidence of spark concentration caused by the debris accumulation phenomenon were found through microscopic analysis on the eroded surfaces. This research also revealed the unexplained phenomenon associated with the undercut that normally formed beneath the PCD cutting edge after erosion. By examining PCD samples using scanning electron microscopy (SEM) and Raman spectroscopy, the formation of the heat-affected layer caused by the high-temperature erosion process in the EDG was analyzed. Results also proved that the surface finish of tungsten carbide (WC) and notch width of the PCD tools, particularly on the tungsten carbide WC/PCD interface, should not be taken as the index to measure PCD tool quality.